Simplifying Medication Regimens for People Receiving Community-Based Home Care Services: Outcomes of a Non-Randomized Pilot and Feasibility Study - Sluggett, Janet K (Clin Interv Aging, 2020)
PURPOSE: Being able to manage a complex medication regimen is key to older people continuing to live at home. This study determined the feasibility of a multi-component intervention to simplify medication regimens for people receiving community-based home care services. PATIENTS AND METHODS: Research nurses recruited people receiving community-based home care services to participate in this non-randomized pilot and feasibility study (Australian New Zealand Clinical Trials Registry ACTRN12618001130257). Participants received a one-off clinical pharmacist intervention comprising medication reconciliation, assessment of capacity to self-manage medications, and application of a structured 5-step tool to identify medication simplification opportunities. A mixed-methods feasibility assessment with an explanatory design was undertaken to assess recruitment, protocol adherence and stakeholder acceptability. Data from interviews with 12 stakeholders were thematically analyzed. Secondary outcome measures, including medication discrepancies, and changes in number of medication administration times per day, quality of life, medication adherence and health service utilization, were determined over a 4-month follow-up. RESULTS: Twenty-five out of the target 50 participants were recruited. Initial recruitment was impacted by apparent uncertain role responsibilities in medication management, with some clients who declined to participate perceiving they would be unlikely to benefit or being reluctant to change regimens. However, with few exceptions, participants who received intervention did so with a high degree of protocol adherence and acceptability. Stakeholders valued the intervention and supported wider implementation. Discrepancies between the baseline medication history from the general medical practitioner and the pharmacist-compiled “best possible medication history” were identified for all participants’ regimens (median of 6 per participant), with one-third resolved at follow-up. Simplification was possible for 14 participants (56%) and implemented for 7 (50%) at follow-up. No significant changes in other secondary outcomes were observed. CONCLUSION: The intervention was delivered as planned, and valued by stakeholders. Recruitment barriers should be addressed before wider implementation.